Africa Agriculture Transformation Scorecard: Performance and Lessons. Namibia - Moyo, T.; Matchaya, Greenwell C.; Uushona, P. (Regional Strategic Analysis and Knowledge Support System for Eastern and Southern Africa, 2023)
The Malabo Declaration on accelerated agricultural growth and transformation for shared prosperity and improved livelihoods is a set of goals that were adopted by Heads of State and Government of the African Union in 2014 in Malabo, Equatorial Guinea (AUC 2014). To translate the seven Malabo commitments into results, a call for action was made by the Heads of State and Governments, by calling upon the AU Commission and the NEPAD Planning and Coordinating Agency, in collaboration with partners, to initiate a review process to be conducted on a biennial basis starting 2017, with an objective of tracking, measuring, and reporting progress towards achieving the Malabo Declaration commitments by 2025. Three Biennial Reviews (BR) have been conducted—the inaugural BR in 2017, the second BR in 2019, and the third and most recent BR in 2021. This brief draws on the third BR report to summarize Namibia’s performance of in pursuit of the seven Malabo Declaration commitments across the three BR cycles, highlights challenges and lessons from the third BR, and outlines policy and programmatic measures required the country to meet the Malabo Declaration commitment targets by 2025. The third BR indicated that overall, Namibia is not on track to achieve the Malabo Declaration commitments by 2025. Despite scoring above the performance benchmark in the inaugural BR, Namibia’s performance has been evaluated as inconsistent across the three BRs to date. A key recommendation of the report is for Namibia to strengthen public spending in the agricultural sector through targeted programs at the national level. Increased spending on agricultural research and development is required. Targeted programs on agricultural finance should be developed as they will improve the performance of the intertwined Malabo commitments on finance (2), hunger (3), poverty (4), and trade (5).